Increase of the RF pulse width in the cavities of the main part of MMF linac - Leontiev, V.N.; Peplov, V.V. (Вопросы атомной науки и техники, 2004)
At the MMF linac for increasing an average beam current an rf pulse width in the accelerating cavities of the main part of the linac have to be increased. Pulse widths of a preamplifier modulator and a high voltage klystron modulator limited this value. Modification of these units allowed increasing the rf pulse width at the klystron output to about 240 µs and the beam pulse duration to 200 µs. An estimation of the maximum possible rf pulse width and the results of an experimental exploration of the upgraded high voltage klystron and preamplifier modulators are presented. A possibility of the longtime stable work with a long pulse is shown.